The Effect of Profitability, Liquidity, and Leverage on Dividend Policy with Firm Size as a Moderating Variable - Susanto, Herry; Rahmawati, Mia Ika (Research Horizon, 2026)
This study aims to examining and analysing how profitability, liquidity, and leverage affect dividend policy is the goal of this study. It also seeks to determine whether business size influences the correlations between these variables. The study focuses on businesses that were part of the Indonesia Stock Exchange’s (IDX) LQ45 index between 2021 and 2024. Purposive sampling was used to choose the sample, and only companies that regularly paid dividends during the observation period were included. The IDX audited yearly financial statements serve as the data source. Data analysis was conducted using multiple linear regression and moderated regression analysis. Profitability and liquidity have a positive and significant effect on dividend policy, while leverage has a negative and significant effect. Firm size strengthens the relationship between liquidity and dividend policy but does not moderate the effects of profitability and leverage. These results highlight how crucial it is for a company to sustain profitability and efficiently manage its capital structure to guarantee the long-term viability of dividend payments. The study’s findings might be considered by investors when evaluating a company’s stability and prospects in light of its size and financial performance.